Primary Pulmonary NUT Carcinoma with NSD3-NUTM1 Fusion. (28th October 2020) - Khan, J; Whaley, R; Cheng, L
Abstract: Casestudy : NUT carcinoma is a rare poorly differentiated carcinoma that is highly aggressive and resistant to multiple treatment modalities. It is estimated to represent 0.6% of non-glandular lung carcinomas. The undifferentiated morphology presents a challenge in arriving at the correct diagnosis, especially on biopsy specimens. Since its original description in 2004, the demographics are shifting to include older individuals and non-midline structures due to the broader availability of ancillary studies. Classically, NUT carcinoma harbors a t(15;19)(q14;p13.1) resulting in the BRD4- NUTM1 fusion gene while other fusion partners are rare. We present a case of primary pulmonary NUT carcinoma with a NSD3-NUTM1 (WHSC1L1-NUTM1) fusion in a 78-year-old male. The patient was lifelong nonsmoker with no significant past medical history who presented with abdominal pain. Imaging revealed 1.4 cm nodule in the right lower lobe. Subsequent biopsy revealed a poorly differentiated squamous cell carcinoma. The neoplastic cells expressed positivity for p40 while lacking expression of TTF1, CK7, CK20, and chromogranin. Resection and lymph node dissection revealed a highly cellular neoplasm composed of epithelioid cells with variable amounts of faintly eosinophilic cytoplasm. Focal keratinization was apparent. The nuclei were plump, vesicular, and fairly uniform with variably prominent nucleoli. Metastatic disease was present in 5 of 5 mediastinal lymph nodes. Adjuvant chemotherapy was planned and next generation sequencing was performed. A NSD3-NUTM1 (WHSC1L1-NUTM1) fusion was discovered and was followed with NUT immunohistochemistry which displayed the characteristic speckled nuclear pattern. Thus refining the original diagnosis to NUT carcinoma. Chemotherapy consisted of cisplatin- gemcitabine and carboplatin-gemcitabine. At last follow-up (7 months) he is alive with no evidence of disease. This case highlights the importance of familiarity with NUT carcinoma and including this rare disease in the differential diagnosis in patients who are lifelong nonsmokers with poorly differentiated lung carcinomas.